2018
DOI: 10.17531/ein.2018.2.04
|View full text |Cite
|
Sign up to set email alerts
|

From "a priori" to "a posteriori" static stability of the slewing superstructure of a bucket wheel excavator

Abstract: The complexity of the slewing superstructure (SS) balancing problem derives from the changeability of its geometric configuration, the complexity of working conditions as well as multiple limitations of the possible set of solutions. Having in mind the fact that the existing reference literature does not fully specify the procedure of static stability proof, the aforementioned procedure is presented in detail for the first time in this paper. A major contribution is represented in the classification of the sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…However, the absolute values of the ordinates of the slewing superstructure CoG are still negligibly small (less than 3.5% of the radius of the calculating contour of the slewing superstructure leaning in the plane of the radiaxial slew bearing). In addition, it was proven in [3] that the impact of the lateral eccentricities of all forces acting upon the slewing superstructure on the safety factors against its overturning is negligibly small. Therefore, the CoG ordinate is excluded from the further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the absolute values of the ordinates of the slewing superstructure CoG are still negligibly small (less than 3.5% of the radius of the calculating contour of the slewing superstructure leaning in the plane of the radiaxial slew bearing). In addition, it was proven in [3] that the impact of the lateral eccentricities of all forces acting upon the slewing superstructure on the safety factors against its overturning is negligibly small. Therefore, the CoG ordinate is excluded from the further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…With all this in mind, it has been concluded that the synthesis of the results of analytical and experimental determination of the slewing superstructure BPSS is absent from the existing literature. The results of the pioneering research presented in papers [2,3] overcome this deficiency. Paper [2] presents an original concept of the corrective mass, based on the synthesis of the results obtained with analytical and experimental methods of determining the slewing superstructure BPSS.…”
Section: Highlights Abstractmentioning
confidence: 99%
See 3 more Smart Citations